INTEGRASI MANAJEMEN PENDIDIKAN SIRKULAR DAN NILAI TAUHID DALAM PENGEMBANGAN SDM ECO-PESANTREN - M. Ilham Faizin Akbar; Siti Aimiah (As-Sulthan Journal of Education, 2026)
The transformation of Eco-Pesantren is often hindered by the low sustainability literacy of educators who remain trapped in linear management paradigms. This study reviews the integration of circular educational management with Tauhid values as a foundation for educator competency development. Using a qualitative case study method, data were collected through in-depth interviews and managerial observations. The results indicate that internalizing Tauhid values combined with circular efficiency principles transforms organizational behavior from consumptive to regenerative. It is concluded that theo-ecological-based HR development creates a spiritually and operationally sustainable educational ecosystem. Consequently, this model can be adopted as a Green HRM framework in Islamic educational institutions to support the achievement of SDGs.